2023
DOI: 10.3390/bioengineering10020253
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal and Neural Stem Cell-Derived Exosomes in Treating Alzheimer’s Disease

Abstract: As the most common form of dementia and a progressive neurodegenerative disorder, Alzheimer’s disease (AD) affects over 10% world population with age 65 and older. The disease is neuropathologically associated with progressive loss of neurons and synapses in specific brain regions, deposition of amyloid plaques and neurofibrillary tangles, neuroinflammation, blood–brain barrier (BBB) breakdown, mitochondrial dysfunction, and oxidative stress. Despite the intensive effort, there is still no cure for the disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…They also offer protection to the nervous system against oxidative damage in several neurological diseases. 23,24 Intranasal (IN) administration of human MSC-derived extracellular vesicles in traumatic brain injury (TBI) mice increases neurogenesis in the sub-ventricular zone (SVZ) by increasing cell proliferation and enhancing the expression of DCX and NeuN. 25 Pourhadi et al also demonstrated that intranasal exosomes reduce amyloid-beta deposits and increase hippocampus preand post-synaptic protein expression to improve spatial memory in Alzheimer's disease model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also offer protection to the nervous system against oxidative damage in several neurological diseases. 23,24 Intranasal (IN) administration of human MSC-derived extracellular vesicles in traumatic brain injury (TBI) mice increases neurogenesis in the sub-ventricular zone (SVZ) by increasing cell proliferation and enhancing the expression of DCX and NeuN. 25 Pourhadi et al also demonstrated that intranasal exosomes reduce amyloid-beta deposits and increase hippocampus preand post-synaptic protein expression to improve spatial memory in Alzheimer's disease model.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, exosomes have the ability to traverse the BBB and stimulate the growth of new neurons in the hippocampus. They also offer protection to the nervous system against oxidative damage in several neurological diseases 23,24 . Intranasal (IN) administration of human MSC‐derived extracellular vesicles in traumatic brain injury (TBI) mice increases neurogenesis in the sub‐ventricular zone (SVZ) by increasing cell proliferation and enhancing the expression of DCX and NeuN 25 .…”
Section: Introductionmentioning
confidence: 99%
“…127 Further, some technological challenges, such as the best administration route and dose, need to be handled. 128 Apart from these limitations, MSC-exosomes may be considered a promising strategy in the therapy of CNS diseases in the future.…”
Section: Mesenchymal Stem Cells and Msc-derived Exosomes Regulate Neu...mentioning
confidence: 99%
“…It is also challenging to identify the specific source of MSC‐exosomes with higher therapeutic potential because of the considerable variations in the disease model, dose, and methods of separation 127 . Further, some technological challenges, such as the best administration route and dose, need to be handled 128 . Apart from these limitations, MSC‐exosomes may be considered a promising strategy in the therapy of CNS diseases in the future.…”
Section: Mesenchymal Stem Cells and Msc‐derived Exosomes Regulate Neu...mentioning
confidence: 99%
“…Additionally, in mouse models, Alvarez‐Erviti et al demonstrated RVG‐targeted exosomes were able to deliver GAPDH siRNA specifically to neurons, microglia and oligodendrocytes with significant knockdown of BACE1 , a target for AD (Alvarez‐Erviti et al, 2011). There has also been recent success in the use of mesenchymal stem cell‐derived exosomes and their ability to ameliorate pathology and improve cognitive function in VAD and AD (Joo et al, 2023; Wang et al, 2023). This potential use of exosomes to deliver therapeutics across the BBB could open new CNS treatment options, if properly explored.…”
Section: Bbb Dysfunction In Dementiamentioning
confidence: 99%